Prevalence and key covariates of non‐medical prescription opioid use among the general secondary student and adult populations in Ontario, Canada. (11th January 2013) - Fischer, Benedikt; Ialomiteanu, Anca; Boak, Angela; Adlaf, Edward; Rehm, Jürgen; Mann, Robert E.
Abstract Introduction and Aims To assess the prevalence and key covariates of non‐medical prescription opioid use (NMPOU) in two representative surveys of adults (Centre for Addiction and Mental Health Monitor, CM) and secondary‐school students (Ontario Student Drug Use and Health Survey, OSDUHS). Design and Methods Data from the 2010 and 2011 cycles (n = 4023) of CM—a stratified, multi‐stage, random‐digit‐dialling telephone survey of adults (18 years and older)—and the 2011 cycle of OSDUHS (n = 3266)—a self‐administered written questionnaire‐based survey of grade 7–12 public system students—were used. Besides NMPOU prevalence, associations were assessed by univariate and multi‐step multivariate (logistic regression) analyses. NMPOU and key socioeconomic (i.e. sex, age, Aboriginal ethnicity, household location, income, subjective social status), health indicators (physical health status, psychological distress, suicidal ideation), drug use (cigarette smoking, binge drinking, cannabis use, other drug use) were measured. Results NMPOU (past year) prevalence was 15.5% in students and 5.9% in adults. Various univariate associations with social, health and drug use factors were found in both populations, with differences by sex. Based on multivariate analyses, other drug use (male students) and rural residence, subjective social status, other drug use and suicidal ideation (female students); marital status and cannabis use (male adults) and binge drinking (female adults) were independently associated with NMPOU in the respective study populations. Discussion and Conclusions NMPOU was high in adults and especially students. Independent predictors of NMPOU were largely inconsistent by sex. Notably, NMPOU is widely distributed across socio‐demographic and ‐economic strata, and thus requires broad‐based interventions.